IMPLEMENTASI PROGRAM LITERASI SEKOLAH DALAM MENINGKATKAN MUTU PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SD YPPSB SANGATTA - Andi Muhammad Fauzan Razak; Khojir Khojir; Nur Kholik Afandi (Al-Rabwah, 2023)
This study aims to describe the implementation of the school literacy program, the supporting factors, and the inhibiting factors in improving the quality of Islamic religious education learning at SD YPPSB Sangatta. Qualitative research methods, with a phenomenological sociology approach. The results of this study indicate that the implementation of the literacy movement program in improving the quality of PAI learning at SD YPPSB Sangatta is through a reading program 10-15 minutes before learning begins and a Al-Qur'an reading program, mandatory visits to the library and gift giving programs, holding literacy competitions and the program to make a writing with their own essays. The improvement in the quality of Islamic religious education learning at SD YPPSB Sangatta can be seen from the increased activeness of students in participating in learning activities, increased activeness in reading, increased concentration in listening and being able to express opinions. The increase in students' abilities can also be seen from students' success in doing work and the school's success in creating hafidzul Qur'an through the Bina Cinta Allah activity. Factors supporting the implementation of the literacy movement program at SD YPPSB Sangatta, namely the existence of suitable facilities and services from the library, availability of learning media, support from foundations, and good school leadership in implementing literacy. While the inhibiting factors are the occurrence of the Covid-19 pandemic, the availability of textbooks that still need to be improved, the lack of interest in reading from students' excessive use of gadgets, and the personal motivation of each student in implementing literacy.